Harnessing Economic Impacts of Migrant Remittances for Development in Sub-Saharan Africa: A Critical Review of the Literature - Nyasulu, Themba (African Human Mobility Review, 2021)
The recent rise in migrant remittances across Sub-Saharan Africa is one of theimportant issues currently dominating economic policy discourse in the region.Given the large volume of remittance flows, it is obvious that they have importantpositive and negative economic effects on the individual families and economiesthat receive them. Therefore, this paper critically examines channels throughwhich remittance transfers affect microeconomic and macroeconomic activity,and suggests policy options available to Sub-Saharan African countries in termsof harnessing their development potential. The paper affirms that prospects forremittances to facilitate economic development remain high provided thatrecipient countries put in place institutional frameworks capable of mitigatingthe malign effects and enhancing the benign effects of remittances.